NUMBER OF BLACK-PIGMENTED ANAEROBIC BACTERIA CONTAINED IN THE GINGIVAL CREVICULAR FLUID (GCF) OF PATIENTS SUFFERING FROM THE CHRONIC PERIODONTITIS AND AGGRESSIVE PERIODONTITIS - Depi Praharani; Peni Pujiastuti; Melok Aris Wahyukundari; Yuliana Mahdiyah Daat Arina; Desi Sandra Sari (Universitas Islam Sultan Agung, 2021)
Background: Chronic Periodontitis (CP) and Aggressive Periodontitis (AP) are chronic inflammation diseases in the dental supporting tissues characterized by the existence of pocket inside, alveolar bone attachments and damages rapidly leading to the dental loss. The pocket inside is related to the existence of the dominating bacteria known as the black-pigmented anaerobic bacteria group. This black-pigmented bacteria group consists of Porphyromonas spp and Prevotella spp genus abundantly found in the periodontal pocket. This research aims at examining the number of black-pigmented bacteria taken from the Gingival Crevicular Fluid (GCF) of patients suffering from the Chronic Periodontitis (CP) and Aggressive Periodontitis (AP). Method: The ethical clearance was obtained from the Faculty of Dentistry, Universitas Jember. The subjects diagnosed with the Chronic Periodontitis (CP) and Aggressive Periodontitis were recorded into pocket and then the panoramic Rontgen photographs were taken. The Gingival Crevicular Fluid (GCF) of patients were taken using a sterile paper point and then inserted to the pocket inside for 30 seconds. The paper point was then inserted to the PBS and examined using a microbiological test on blood agar media. The mouth cavity hygiene levels of subjects were recorded using OHI-S, while the needs on periodontal treatments using CPITN. The statistical test was conducted using T-test with the value of p<0.05. Result: he result shows that subjects suffering from the Chronic Periodontitis (CP) and Aggressive Periodontitis (AP) had the pocket depth differences yet not significant (p>0.05). this shows the same periodontal disease severity of both Chronic Periodontitis (CP) and Aggressive Periodontitis (AP). The bacteria culture result shows that the number of black- pigmented anaerobic bacteria in both Chronic Periodontitis (CP) and Aggressive Periodontitis (AP) was not significant (p>0.05). The mouth hygiene level of patients suffering from the Chronic Periodontitis (CP) and Aggressive Periodontitis (AP) was at the medium (93%) level with the needs on periodontal treatments of scaling and root planning (85%) Conclusion: The number of black-pigmented anaerobic bacteria colonies belonging to the patients suffering from the Chronic Periodontitis (CP) and Aggressive Periodontitis (AP) was same.